2014
DOI: 10.1002/ana.24100
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal cerebral ischemia triggers dysmaturation of caudate projection neurons

Abstract: Objective Recently we reported that the neocortex displays impaired growth after transient cerebral hypoxia-ischemia (HI) at preterm gestation that is unrelated to neuronal death but is associated with decreased dendritic arbor complexity of cortical projection neurons. We hypothesized that these morphological changes constituted part of a more widespread neuronal dysmaturation response to HI in the caudate nucleus (CN), which contributes to motor and cognitive disability in preterm survivors. Methods Ex viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 64 publications
4
55
0
Order By: Relevance
“…Both DSs and PNNs have been involved in the regulation of synaptic connectivity and plasticity [43][44][45][46]. Our results showing decreased DS levels in IUGR rabbits are in line with previously described studies on guinea pig and sheep model showing changes in DS density and morphology along with changes in synaptic receptors after acute and chronic intrauterine insults [16,[47][48][49]. On the contrary, although there is growing interest in the description of PNN alterations related to specific brain diseases such as Alzheimer disease, schizophrenia, and epilepsy [45,50], the pattern of alterations in the PNNs related to IUGR had not been previously evaluated.…”
Section: Discussionsupporting
confidence: 91%
“…Both DSs and PNNs have been involved in the regulation of synaptic connectivity and plasticity [43][44][45][46]. Our results showing decreased DS levels in IUGR rabbits are in line with previously described studies on guinea pig and sheep model showing changes in DS density and morphology along with changes in synaptic receptors after acute and chronic intrauterine insults [16,[47][48][49]. On the contrary, although there is growing interest in the description of PNN alterations related to specific brain diseases such as Alzheimer disease, schizophrenia, and epilepsy [45,50], the pattern of alterations in the PNNs related to IUGR had not been previously evaluated.…”
Section: Discussionsupporting
confidence: 91%
“…106 However, reduced growth of the caudate was not explained by loss of GABAergic interneurons or projection neurons. Reduced growth of the cerebral cortex and the caudate was also not related to loss of cortical pyramidal neurons 107 or medium spiny projection neurons in the caudate, 108 which comprise the majority of neurons in each region.…”
Section: Pathogenesis Of Gray Matter Abnormalitiesmentioning
confidence: 84%
“…In addition to the previously reported mechanisms, including impairments of various cellular components, such as the dendritic arbor and synapse formation of neurons, and myelination failure (9,13,15), defective neuronal alignment is presumed to be another mechanism underlying the later development of cognitive impairment in the extremely preterm infants. Neuronal migration and alignment may also be affected in other brain regions besides the neocortex.…”
Section: Discussionmentioning
confidence: 97%
“…Disturbances of maturation of various cellular components of the cortical neurons, such as the dendritic arbors and synapse formation, have been shown to be related to impaired cerebral growth in a preterm large-animal model (13). Recent studies have also suggested perturbed maturation of inhibitory interneurons, caudate projection neurons, and astrocytes by using animal models (14)(15)(16). Furthermore, as an underlying cause of the altered brain growth and subsequent development of cognitive dysfunction, brain injury in premature infants is thought to affect radial neuronal migration in the neocortex (17); however, this idea has not yet been rigorously investigated (6).…”
Section: Many Extremely Preterm Infants (Born Before 28 Gestational Wmentioning
confidence: 99%
See 1 more Smart Citation